2022
DOI: 10.1039/d2sc04196k
|View full text |Cite
|
Sign up to set email alerts
|

Promoting halogen-bonding catalyzed living radical polymerization through ion-pair strain

Abstract: Discovering efficient catalysts is highly desired in expanding the application of halogen-bonding catalysis. We herein report our findings on applying triaminocyclopropenium (TAC) iodides as highly potent catalysts for halogen-bonding catalyzed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Recently, Liu and co-workers demonstrated the use of triaminocyclopropenium (TACP) iodides as an ion-pair catalyst in halogen-bonding catalyzed living radical polymerization . The iodine anion of the TACP iodide activates iodine-terminated polymers, resulting in the generation of propagating radicals.…”
Section: Depolymerization From Controlled Polymerization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Liu and co-workers demonstrated the use of triaminocyclopropenium (TACP) iodides as an ion-pair catalyst in halogen-bonding catalyzed living radical polymerization . The iodine anion of the TACP iodide activates iodine-terminated polymers, resulting in the generation of propagating radicals.…”
Section: Depolymerization From Controlled Polymerization Methodsmentioning
confidence: 99%
“…GPC traces obtained from the samples: before reaction (black line); reacted at 120 °C for 24 h with TACP-I as catalyst (red line); reacted at 150 °C for 24 h with TACP-I as catalyst (blue line). Figure adapted with permission from Royal Society of Chemistry from ref , copyright 2022; permission conveyed through Copyright Clearance Center, Inc.…”
Section: Depolymerization From Controlled Polymerization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] In order to achieve an efficient unzipping of the polymer chains, high endgroup fidelity has to first be ensured during the respective polymerizations as minimal, if any, depolymerization can be observed when these end-groups are removed. 12,13 As such, the vast majority of investigated depolymerizable polymers were synthesized by either reversible addition-fragmentation chaintransfer (RAFT) polymerization or atom transfer radical polymerization (ATRP), [12][13][14][15][16][17][18][19] two of the most widely used RDRP techniques. [20][21][22][23] In seminal independent works by the groups of Gramlich 18 and Raus, 24 they showed that the depolymerization of bottlebrush polymers synthesized by either RAFT or ATRP was possible at relatively low temperatures (70 °C and 90 °C respectively).…”
Section: Introductionmentioning
confidence: 99%
“…This is shown by the fact that minimal depolymerization was observed when the end-groups were removed. 12,13 As such, the vast majority of investigated depolymerizable polymers were synthesized by either reversible addition–fragmentation chain-transfer (RAFT) polymerization or atom transfer radical polymerization (ATRP), 12–19 two of the most widely used RDRP techniques. 20–23…”
Section: Introductionmentioning
confidence: 99%